Organotin Exposure and Vertebrate Reproduction: A Review - de Araújo, Julia Fernandez Puñal; Podratz, Priscila Lang; Merlo, Eduardo; Sarmento, Isabela Valim; da Costa, Charles Santos; Niño, Oscar Mauricio Santamaria; Faria, Rodrigo Alves; Freitas Lima, Leandro Ceotto; Graceli, Jones Bernardes (Frontiers in Endocrinology, 2018)
Organotin compounds (OTs) are organometallic compounds that are widely used in industry, such as in the manufacture of plastics, pesticides, paints, and others. OTs are released into the environment by anthropogenic actions, leading to contact with aquatic and terrestrial organisms that occurs in animal feeding. Although OTs are degraded environmentally, reports have shown over the years the effects of this contamination because it can affect organisms of different trophic levels. OTs act as endocrine-disrupting chemicals (EDCs), which can lead to several abnormalities in organisms. In male animals, OTs decrease the weights of the testis and epididymis and reduce the spermatid count, among other dysfunctions. In female animals, OTs alter the weights of the ovaries and uteri and induce damage to the ovaries. In addition, OTs prevent fetal implantation and reduce mammalian pregnancy rates. OTs cross the placental barrier and accumulate in the placental and fetal tissues. Exposure to OTs in utero leads to the accumulation of lipid droplets in the Sertoli cells and gonocytes of male offspring in addition to inducing early puberty in females. In both genders, this damage is associated with the imbalance of sex hormones and the modulation of the hypothalamic-pituitary-gonadal axis. Here, we report that OTs act as reproductive disruptors in vertebrate studies; among the compounds are TeBT (tetrabutyltin), TBTCl (tributyltin chloride), TBTAc (tributyltin acetate), TPTCl (triphenyltin chloride), TPTOH (triphenyltin hydroxide), DBTCl (dibutyltin chloride), DBTCl2 (dibutyltin dichloride), DPTCl2 (diphenyltin dichloride), MBT (monobutyltin), and azocyclotin.